CONTROL SISTEM INKUBATOR TELUR AYAM MENGGUNAKAN METODE FUZZY LOGIC - Mufidatul islamiyah; Samsul Arifin (P3M Politeknik Negeri Banjarmasin, 2023)
Technology is currently developing very rapidly, one of which is the technology of hatching eggs in chicken farms. The technology used is a chicken egg incubator why do farmers need an incubator in hatching because many farmers experience hatch failure, so that crop failure does not occur, this incubator is designed to achieve an ideal temperature of 37-40 0C, this ideal temperature is a good temperature in hatching chicken eggs, if it is too hot it will cause the quality of the eggs to decrease and even cause death. Controlling the temperature in this incubator uses the fuzzy mamdani and the DS18B20 sensor. The DS18B20 sensor is used to get the temperature in the incubator as input for fuzzy logic, the output of this system is the fan speed (PWM) and lights to make the temperature warmer. Based on the simulation results using fuzzy logic at a normal temperature of 39.5 0C with a total of 25 eggs the fan speed reaches normal, namely 160 PWM.